Governing Extreme Poverty at the Local Level: A Thematic Network Study from Jeneponto, Indonesia - Widyawati, ‎; Sangkala, ‎; Rusdi, Muhammad; Ibrahim, Muh. Akmal; Susanti, Gita (KnE Social Sciences, 2025)
This study examines the dynamics of local governance in extreme poverty alleviation efforts in Jeneponto District, Indonesia, one of the national priority areas for accelerating the eradication of extreme poverty. Using a qualitative case study approach, this study integrates document analysis and in-depth interviews with stakeholders from local government and the community. The analysis process was conducted using Atlas. Ti software version 23 through a word frequency approach and thematic network mapping to visualize patterns of relations between actors, institutions, and governance mechanisms. Key findings identify seven interrelated thematic clusters: 1. Planning and policy frameworks. 2. Program implementation and evaluation. 3. Cross-sector collaboration. 4. Contextual innovation and solutions. 5. Public communication and participation. 6. Data governance. 7. Structural barriers. Although planning documents formally prioritize poverty alleviation, the absence of a specific nomenclature for “extreme poverty,” fragmentation of data systems, and institutional rigidities have hampered program effectiveness. Local innovation has not been integrated into the formal planning system, while sectoral egos and weak coordination structures hamper collaboration between sectors. This study enriches the theoretical discourse on integrative and adaptive governance by showing how institutional fragmentation, low data interoperability, and limited participatory mechanisms limit the capacity of local responses to the complexities of extreme poverty. Key recommendations include institutionalizing innovation, building integrated data systems across sectors, and strengthening inclusive, evidence-based, and reflective governance of socio-economic vulnerabilities at the local level.